1999
DOI: 10.1016/s0735-1097(99)00062-5
|View full text |Cite
|
Sign up to set email alerts
|

Marked elevation of myocardial trace elements in idiopathic dilated cardiomyopathy compared with secondary cardiac dysfunction

Abstract: A large, significant increase of myocardial TE is present in IDCM but not in secondary cardiac dysfunction. The increased concentration of TE in pts with IDCM may adversely affect mitochondrial activity and myocardial metabolism and worsen cellular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 25 publications
1
55
0
3
Order By: Relevance
“…As an example, a recent report on trace elements in idiopathic dilated cardiomyopathy (IDCM) showed an increase of > 10,000 times more mercury in myocardial tissue than in skeletal muscle in all patients with this condition. The mean mercury level in cardiac muscle was 22,000 times higher in IDCM patients than in control subjects (178.4 µg/g vs. 0.008 µg/g; Frustaci et al 1999).…”
Section: Discussionmentioning
confidence: 85%
“…As an example, a recent report on trace elements in idiopathic dilated cardiomyopathy (IDCM) showed an increase of > 10,000 times more mercury in myocardial tissue than in skeletal muscle in all patients with this condition. The mean mercury level in cardiac muscle was 22,000 times higher in IDCM patients than in control subjects (178.4 µg/g vs. 0.008 µg/g; Frustaci et al 1999).…”
Section: Discussionmentioning
confidence: 85%
“…It has been suggested that it may play a role in the pathogenesis of many cardiovascular diseases such as arteriosclerosis, idiopathic dilated cardiomyopathy and hypertension [21][22][23] . In a recent epidemiologic study, it has been reported that chronic Cd exposure may have increased the blood pressure and the risk of hypertension in the general adult Korean population [24] .…”
Section: Discussionmentioning
confidence: 99%
“…[31] Baz› kalp yetersizli¤i olgular›nda kalp dokusunda önemli miktarda (kontrollerin 22.000 kat›) c›va birikimi saptanm›flt›r. [32] 5-7 y›l süren insan çal›flmalar›nda amalgam dolgular›n böbrek fonksiyonlar›na etkisine dair hiçbir kan›t bulunamam›flt›r, [33] ne var ki, tam tersi sonuçlara ulaflan ça-l›flmalar da mevcuttur. [34] Hayvan deneylerinde, amalgam dolgu nedeniyle böbrek fonksiyonlar›n›n bozuldu¤u gö-rülmüfltür.…”
Section: Discussionunclassified